Performance Audit of Pradhan Mantri Swasthya Suraksha Yojana - CAG of India (CAG of India, 2018)
The Pradhan Mantri Swasthya Suraksha Yojana was announced in August 2003 with the objective of correcting imbalances in the availability of tertiary care hospitals/medical colleges providing super speciality services and improving the quality of medical education in India. A performance audit, covering the period 2003 to 2017, was conducted to assess how far the objectives of the Scheme were achieved and whether the available resources were utilised in an economic, efficient and effective manner. It also suggests ways to bring about improvement in programme delivery. https://cag.gov.in/uploads/download_audit_report/2018/Report_No_10_of_2018_-_Performance_Audit_on_Pradhan_Mantri_Swasthya_Suraksha_Yojana_in_Ministry_of_Health_and_Family_Welfare.pdf
For the period 2003-04 to 2016-17